Analisis Kualitas Pelayanan Kesehatan di Puskesmas Porong Kabupaten Sidoarjo - Amirotul Luthfiyah; Imelda Dian Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Public service is crucial for fulfilling community basic needs, particularly in healthcare. Puskesmas Porong, a healthcare institution in Sidoarjo District, serves as the primary focus of this study. With a vision to provide quality and professional healthcare services to the community, Puskesmas Porong plays a pivotal role as the primary healthcare center in Porong Subdistrict. Despite adequate facilities including 46 inpatient beds and coverage of 10 surrounding villages, challenges persist. High patient influx poses significant issues such as long waiting times for services, attributed to insufficient staff and resources. Moreover, limited community participation in providing feedback is a concern, hindering the identification of issues and optimal solutions for healthcare service improvement.This qualitative research aims to analyze healthcare service quality at Puskesmas Porong, employing interviews with key stakeholders including the head of the health center, medical staff, administrative personnel, and patients. Additionally, observation and documentation methods were utilized to gather comprehensive data on service provision, patient satisfaction, and facility conditions. Results reveal that while operational procedures are generally adhered to, discrepancies exist between management perceptions and patient experiences. Patients highlight shortcomings in BPJS utilization, medical equipment adequacy, and diagnostic accuracy, underscoring the need for targeted improvements to enhance service quality and community trust.